2006
DOI: 10.1097/01.tp.0000225830.76907.d0
|View full text |Cite
|
Sign up to set email alerts
|

Valganciclovir Preemptive Therapy for the Prevention of Cytomegalovirus Disease in High-Risk Seropositive Solid-Organ Transplant Recipients

Abstract: VGCV is safe and highly efficacious in the prevention of CMV disease in high-risk seropositive organ transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Six of the nine studies described explicitly the relationship between preemptive therapy and subsequent development of CMV disease (22,23,27,30,31,33,34) (22,23,26,27,(29)(30)(31)(32)(33). Five studies reported subsequent follow-up for 39 patients with recurrence after preemptive valganciclovir use for their first episodes of viremia (23,27,(30)(31)(32). Two patients developed CMV disease (27) (27).…”
Section: Cytomegalovirus (Cmv) Is An Important Opportunistic Pathogenmentioning
confidence: 99%
See 4 more Smart Citations
“…Six of the nine studies described explicitly the relationship between preemptive therapy and subsequent development of CMV disease (22,23,27,30,31,33,34) (22,23,26,27,(29)(30)(31)(32)(33). Five studies reported subsequent follow-up for 39 patients with recurrence after preemptive valganciclovir use for their first episodes of viremia (23,27,(30)(31)(32). Two patients developed CMV disease (27) (27).…”
Section: Cytomegalovirus (Cmv) Is An Important Opportunistic Pathogenmentioning
confidence: 99%
“…CMV disease developed in 15.5% (17/110) of the patients receiving these agents and 0% (0/187) of those not receiving (23,28). (30,31). Similarly, the threshold of DNAemia by CMV DNA PCR to initiate preemptive treatment varied from ≥15 to ≥2000 copies/mL (23,(27)(28)(29)(32)(33)(34).…”
Section: Cytomegalovirus (Cmv) Is An Important Opportunistic Pathogenmentioning
confidence: 99%
See 3 more Smart Citations